Complex Dynamics of a Prey-predator System Incorporating Functional Response Dependent Prey Refuge with Harvesting - Jana, Soovoojeet; Guria, Srabani; Ghorai, Abhijit; Kar, Tapan Kumar (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we consider a prey-predator system allowing prey refuge and harvesting the prey species only. It is investigated under which condition the system has no limit cycle. An optimal harvesting policy is also formulated using Pontryagin's Maximum Principle. A comparison study have been done with the model in which the per individual prey refuge taken as constant. We investigate one and two parametric bifurcations thoroughly. Here we also discuss the bi-stability of the model in brief when the interior equilibrium is not unique. Some numerical simulations are given to verify our analytic works.